Hsa_circ_0020491 promotes polycystic ovary syndrome by interacting with IGF2BP2 through regulation of granular cell autophagy and mitochondrial dysfunction - XiaLing Huang; Fen Yu (Gynecological Endocrinology)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder in women, yet its underlying mechanisms remain incompletely understood. This study investigated the role of hsa_circ_0020491 in PCOS pathogenesis, focusing on granulosa cells (GCs). Analysis of GCs from PCOS patients and controls revealed significant upregulation of both hsa_circ_0020491 and IGF2BP2, with their expression levels positively correlated. In a dihydrotestosterone (DHT)-treated KGN cell model of PCOS, silencing either circ_0020491 or IGF2BP2 mitigated autophagy dysregulation and mitochondrial dysfunction, evidenced by altered autophagy-related proteins, mitochondrial membrane potential, ATP levels, mtDNA content, and reactive oxygen species. Mechanistically, circ_0020491 binds to and stabilizes IGF2BP2, amplifying its effects. Overexpression of IGF2BP2 counteracted the improvements induced by circ_0020491 knockdown. In vivo, a dehydroepiandrosterone (DHEA)-induced PCOS mouse model confirmed that circ_0020491 suppression attenuated disease progression, improved mitochondrial function, and reduced excessive autophagy. These findings demonstrate that hsa_circ_0020491 exacerbates PCOS by interacting with IGF2BP2 to disrupt autophagy and mitochondrial homeostasis in GCs, offering a potential therapeutic target.